American Christianity : the continuing revolution - Cox, Stephen D., 1948- (Discovering America series., 2014)
Stephen Cox argues that American Christianity is a revolution that is always happening, and always needs to happen. The old-time religion always has to be made new, and that is what Americans have been doing throughout their history. --from publisher description.